Guidelines for Modeling Expressivity in Virtual Patients for Healthcare Training - Ferreira, Wesley Ferreira de; Nedel, Luciana (Anais Estendidos da Conference on Graphics, Patterns and Images (SIBGRAPI); 2025: Anais Estendidos da XXXVIII Conference on Graphics, Patterns and ImagesDO - 10.5753/sibgrapi.est.2025.38326, 2025)
Virtual patients are increasingly being used in healthcare education to support the development of communication and social skills. However, their effectiveness depends on the integration of expressive realism across verbal and nonverbal communication modalities. This paper proposes a set of guidelines for modeling emotional expressivity in virtual patients by combining facial expressions, body posture, and vocal prosody. Grounded in established affective science literature—including Ekman’s basic emotions, the Facial Action Coding System (FACS), the Body Action and Posture (BAP) framework, and GeMAPS acoustic parameters—these guidelines synthesize expressive features for six core emotions: joy, sadness, anger, fear, disgust, and surprise. Our goal is to support the development of emotionally expressive virtual patients for medical simulations and virtual reality training.